2018
DOI: 10.1177/1947603518767998
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Well-Rounded Exercise Program on Systemic Biomarkers Related to Cartilage Metabolism

Abstract: Nonsurgical treatment such as exercise is the preferred method for management of knee osteoarthritis (OA). A combination of aerobic, muscle strengthening, and flexibility exercises is recommended for older adults. However, effects of the exercise intervention on cartilage metabolism remain unclear. This study used biomarkers to investigate the effects of well-rounded exercise program on cartilage metabolism in 42 women (mean age: 59 years). Participants started a weekly supervised exercise program and continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Further reduction was shown when adding 30 minutes of whole‐body vibration exercise . Likewise, Azukizawa et al showed reduced CTX‐II level at 24 weeks after a well‐rounded exercise program with one weekly supervised exercise class the first 12 weeks followed by a 12‐week period of encouraged self‐training. In contrast, Petersen et al and Hunt et al found no significant change in CTX‐II levels after 12 weeks of supervised progressive quadriceps strength training at 3 times weekly (70%‐80% of 1 RM), respectively, 10 weeks of lower extremity strength training (10 RM) performed a minimum of 4 days per week at home and supervised 5 times.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Further reduction was shown when adding 30 minutes of whole‐body vibration exercise . Likewise, Azukizawa et al showed reduced CTX‐II level at 24 weeks after a well‐rounded exercise program with one weekly supervised exercise class the first 12 weeks followed by a 12‐week period of encouraged self‐training. In contrast, Petersen et al and Hunt et al found no significant change in CTX‐II levels after 12 weeks of supervised progressive quadriceps strength training at 3 times weekly (70%‐80% of 1 RM), respectively, 10 weeks of lower extremity strength training (10 RM) performed a minimum of 4 days per week at home and supervised 5 times.…”
Section: Discussionmentioning
confidence: 97%
“…These results could indicate that exercise‐induced changes in CTX‐II level are not related to training intensity in patients with knee OA. OA‐severity may have played a role since Azukizawa et al showed different training response in patients with pre‐radiological knee OA (KL grade 0‐1) and radiological knee OA (KL grade ≥2). Exercises induced reduction in CTX‐II level was only present in the patients with pre‐radiological OA while CTX‐II level was unchanged in those with radiological OA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with their connective tissue, affected by degenerative or autoimmune diseases, are subject to periods of acute crisis that make simple movements painful and more elaborate movements impossible. Consequently, it makes the physical activity practice a challenge [1][2][3].…”
Section: Introductionmentioning
confidence: 99%